INTEGRASI MADRASAH DINIYAH TAKMILIYAH PADA SEKOLAH NEGERI (ALTERNATIF PENGUATAN PENDIDIKAN KARAKTER SISWA PASCA BERLAKUNYA PERATURAN PRESIDEN NOMOR 87 TAHUN 2017 TENTANG PENDIDIKAN KARAKTER) - Mumtahanah, Nurotun (Universitas Islam Lamongan, 2017)
This study is based on the lack of learning hours of PAI with many material and lack of public attention with non formal education such as Madrasah Diniyah Takmiliyah and less optimal religious education for the students of the State. From those backgrounds, the writer encourages explorers to explore the issues of how the implementation, achievements, supporting factors and inhibitors of Madrasah Diniyah Takmiliyah Model are integrated in the State School. This study aims to explain the prediction of the implementation, explain the achievements, and explain the supporting factors and factors inhibiting Madrasah Diniyah Takmiliyah Integrated in School Affairs. Based on the above background, what is to be disclosed in this paper is how the integration effort of madrasah diniyah takmiliyah in public school as an effort to strengthen character education of students post-Presidential Regulation number 87 year 2017 about character education. The study concludes that the integration of Madrasah Diniyah Takmiliyah in the School of Schools as an effort to strengthen the education of the character of the students after the Presidential Regulation number 87 of 2017 on character education can be done in the following way: First, integrate the sub-system of Madrasah Diniyah Takmiliyah at Sekolah Negeri in time after the school's learning activities are over; Second, integrate the methods used in conventional and unconventional PAIs; Third, develop the subjects of PAI, to be some of the same material in madrasah diniyah, namely Al Qur'an and Hadith, Aqidah, Akhlak, Fiqh, Tarikh or History of Islamic Culture.Keywords: Integration, Madrasah Diniyah Takmiliyah, Presidential Regulation No. 87 of 2017, Character Education.